2012
DOI: 10.1016/j.gloenvcha.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in cyclone preparedness and relief efforts in coastal Bangladesh: Lessons for climate adaptation?

Abstract: T his a r tic le se e k s to d ra w p o s sib le le ss o n s for a d a p ta tio n p r o g r a m m e s in B a n g la d esh b y e x a m in in g w h e th e r c y c lo n e p r e p a r ed n e ss an d r e lie f in te r v e n tio n s are su b je c t to corru p t p r a c tic e s. B ased o n a r a n d o m sa m p le su r v ey o f 2 7 8 h o u se h o ld s, th re e fo c u s-g r o u p d is c u s sio n s an d s e v e n k e y -in fo r m a n t in te r v ie w s, th e a rticle in v e s tig a te s th e n atu re an d e x te n t o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…5 In fact, Mahmud and Prowse (2012) find that the allocation of relief programs suffered from corruption during Cyclone Aila in Bangladesh. If this is the case, the households which are severely affected by the disaster but cannot receive the relief are likely to experience transient poverty.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In fact, Mahmud and Prowse (2012) find that the allocation of relief programs suffered from corruption during Cyclone Aila in Bangladesh. If this is the case, the households which are severely affected by the disaster but cannot receive the relief are likely to experience transient poverty.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Since five households were unavailable for the survey, I obtained 427 of 432 sample households from 24 para. The total sample size and studied villages in this study is comparable or larger than the other quantitative and qualitative studies on Cyclone Aila, such as Mallick and Vogt (2012;, Saha (2015), Mahmud and Prowse (2012), Sultana and Mallick (2015) and Mallick et al (2011). Appendix Table A1 Satkhira.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, corrupt practices have contaminated public procurements (Mahmood 2010), health and education services (Knox 2009), and cyclone preparedness (Mahmud and Prowse 2012). As a result, citizen distrust of the state is high and the country's economic growth has been impaired.…”
Section: National Variations In Asian Corruptionmentioning
confidence: 99%
“…As Alam and Collins (2010) point out, insufficient shelters in the unplanned settlement areas exacerbate livelihood vulnerability. For instance, a survey of 278 households in the coastal district of Khulna revealed that less than 5% of those considered ultra-poor had access to the shelters during cyclone Alia (Mahmud and Prowse 2012). Although the exact proportion of urban migrants is not known in Cox's Bazar, based on the average household size of 4.4 people in Bangladesh (BBS 2012c) and an approximation by a locally operating non-government organisation (NGO) called Mukti Cox's Bazar (MCB) that there are 6665 slum households in the district (MCB 2012), we estimate that there are around 30,000 slum people in the district.…”
Section: Contemporary South Asia 295mentioning
confidence: 99%